Education Budget Management, New Public Management and the COVID-19 Pandemic - Arwinda Putri Amalia (Dinamika Pendidikan)
This paper aims to describe the management of education budget in a private school during the pandemic and how the New Public Management sight. How do a private school with very limited budget resources during the pandemic survives and controls spending with minimal amounts of income and how the New Public Management concept views the Education Budget management process in a private school seen from the government's role in helping schools meet their budget needs. This study had been observed in Muhammadiyah Vocational High School in Purwokerto used a qualitative perspective and deep interviews to collect the information. The result of this research is the private school with limited funding sources has an ability to apply the new public management concept and the government as the provider of development funding assistance made this school could compete with other private schools and public schools, moreover, the school is able to manage a limited education budget during a pandemic.